Alteration‐Induced Volcano Instability at La Soufrière de Guadeloupe (Eastern Caribbean). Issue 8 (15th August 2021) - Heap, Michael J.; Baumann, Tobias S.; Rosas‐Carbajal, Marina; Komorowski, Jean‐Christophe; Gilg, H. Albert; Villeneuve, Marlène; Moretti, Roberto; Baud, Patrick; Carbillet, Lucille; Harnett, Claire; Reuschlé, Thierry
Abstract: Volcanoes are unstable structures that deform laterally and frequently experience mass wasting events. Hydrothermal alteration is often invoked as a mechanism that contributes significantly to volcano instability. We present a study that combines laboratory experiments, geophysical data, and large‐scale numerical modeling to better understand the influence of alteration on volcano stability, using La Soufrière de Guadeloupe (Eastern Caribbean) as a case study. Laboratory experiments on variably altered (advanced argillic alteration) blocks show that uniaxial compressive strength, Young's modulus, and cohesion decrease as a function of increasing alteration, but that the internal friction angle does not change systematically. Simplified volcano cross sections were prepared (a homogenous volcano, a volcano containing the alteration zone identified by a recent electrical survey, and a volcano with an artificially enlarged area of alteration) and mechanical properties were assigned to zones corresponding to unaltered and altered rock. Numerical modeling performed on these cross sections, using a hydro‐thermo‐mechanical modeling code, show (a) the importance of using upscaled values in large‐scale models and (b) that alteration significantly increases volcano deformation and collapse volume. Finally, we combined published muon tomography data with our laboratory data to create a 3D strength map, exposing a low‐strength zone beneath the southern flank of the volcano coincident with the hydrothermal system. We conclude that hydrothermal alteration decreases volcano stability and thus expedites volcano spreading and increases the likelihood of mass wasting events and associated volcanic hazards. Hydrothermal alteration, and its evolution, should therefore be monitored at active volcanoes worldwide. Plain Language Summary: The rocks forming a volcanic edifice can be altered by circulating hydrothermal fluids. This alteration can influence the physical and mechanical properties of these rocks, which could jeopardize volcano stability. The stability of a volcanic edifice is an important consideration in volcanic hazards and risk assessments due to the potentially dire consequences of partial volcanic flank collapse. Using a combination of experimental data, geophysical data, and modeling, and La Soufrière de Guadeloupe (Eastern Caribbean, France) as a case study, we find that hydrothermal alteration decreases volcano stability and thus promotes volcano instability and associated volcanic hazards. As a result, we conclude that hydrothermal alteration, and its evolution, should be monitored at active volcanoes worldwide. Key Points: Laboratory experiments show that hydrothermal alteration reduces the strength of volcanic rock from La Soufrière Numerical modeling shows that hydrothermal alteration significantly increases volcano deformation and collapse volume We provide a 3D strength map of La Soufrière that exposes a low‐strength zone coincident with the hydrothermal system